Perovskite solar cell based on tin-based perovskite thin film and preparation method
By introducing two-dimensional perovskite single crystals into tin-based perovskites, adjusting phase distribution and optimizing the crystallization process, the poor carrier transmission and non-radiative recombination problems caused by low n-value phases in tin-based perovskites are solved, and the efficiency and stability of tin-based perovskite solar cells are significantly improved.
Patent Information
- Application Number
- CN202411969104.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The addition of large organic cations to the tin-based perovskite forms an undesirable low n-value phase, resulting in poor carrier transmission and intensified non-radiative recombination, which damages the performance of solar cells.
Two-dimensional perovskite single crystals are introduced to regulate the distribution of two-dimensional phases and three-dimensional phases in tin-based perovskites, optimize the crystallization process, and prepare high-quality tin-based perovskite films and efficient and stable solar cells.
By optimizing the phase distribution and crystallization process, the defect density and non-radiation losses are reduced, the carrier extraction and transmission capacity is improved, and the efficiency and stability of solar cells are significantly improved. The maximum conversion efficiency increases from 10.91% to 13.28%, and the initial efficiency of 96% is maintained after 3000 hours.
Smart Images

Figure CN119789740A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials and devices, and in particular relates to a perovskite solar cell based on a tin-based perovskite film and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, energy shortages and environmental pollution are receiving increasing attention. Photovoltaic technology, which harnesses solar energy to generate electricity without harming the environment, has attracted widespread attention as a green energy technology. Currently, silicon-based photovoltaic technology has achieved a power conversion efficiency of 27.09%, approaching the theoretical limit of single-junction solar cells. As low-cost alternatives to silicon-based photovoltaics, thin-film photovoltaics and emerging photovoltaic technologies are being widely explored. These technologies are based on various light-absorbing materials, such as chalcogenide semiconductors, organic semiconductors, quantum dots, dyes, and halide perovskites. Although all of these mainstream photovoltaic technologies still lack the efficiency and stability of market-leading silicon-based photovoltaics, they offer lower carbon emissions and faster energy payback periods, which holds great promise for various photovoltaic technologies.
[0003] Over the past decade, the outstanding photovoltaic performance of metal halide perovskite solar cells has highlighted their potential, with power conversion efficiencies increasing from an initial 3.8% to over 26% today. However, the long-term operational stability and toxicity of lead-based halide perovskites have hindered their further widespread application. Tin-based perovskites theoretically possess comparable or even superior optoelectronic performance to lead-based perovskites due to their low toxicity, band gaps close to the theoretical limit, smaller exciton binding energies, and higher carrier mobility. However, the facile oxidation of divalent tin to tetravalent tin and the difficulty in controlling the crystallization process of tin-based perovskites lead to high defect densities and severe p-type doping, ultimately compromising device efficiency and stability.
[0004] To this end, the introduction of various large organic cations, such as phenylethylamine and ethylenediamine, into the tin-based perovskite system can reduce p-type self-doping and improve the stability of tin-based perovskite solar cells. However, the introduction of large organic cations will form a low-n phase, inhibiting carrier transport and aggravating non-radiative recombination, which will impair the performance of tin-based perovskite solar cells. Summary of the Invention
[0005] In response to the technical problems that the addition of large organic cations to tin-based perovskites forms an undesirable low-n-value phase, resulting in poor carrier transport in the perovskite film and aggravated non-radiative recombination, the purpose of the present invention is to propose a method for introducing two-dimensional perovskite single crystals to adjust the distribution of two-dimensional and three-dimensional phases in the tin-based perovskite, optimize the crystallization process, and prepare high-quality tin-based perovskite films and efficient and stable tin-based perovskite solar cells. The prepared tin-based perovskite solar cell has the characteristics of good phase distribution, slow crystallization rate, less non-radiative recombination, and fast interface carrier extraction and transmission.
[0006] The present invention is achieved through the following technical solutions.
[0007] In one aspect of the present invention, a method for preparing a perovskite solar cell based on a tin-based perovskite film is provided, comprising the following steps:
[0008] (1) Cleaning and baking the etched ITO conductive glass to obtain a clean ITO substrate;
[0009] (2) dissolving the interface modification layer material in a mixed solvent of isopropyl alcohol and toluene to prepare an interface modification layer precursor solution;
[0010] (3) dissolving a two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride, and phenethylammonium bromide in a mixed solvent A in a molar ratio of (0.01-0.05):(0.90-1.00):(0.90-1.00):(0.05-0.10):(0.10-0.50):(0.05-0.10) to prepare a tin-based perovskite precursor solution;
[0011] (4) spin coating a hole transport layer material on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer;
[0012] (5) using an anti-solvent method to spin-coat a tin-based perovskite precursor solution onto an ITO transparent conductive glass deposited with a hole transport layer material, and annealing to obtain a tin-based perovskite film;
[0013] (6) spin coating an interface modification layer material on the tin-based perovskite film to deposit an interface modification layer;
[0014] (7) vacuum thermal evaporation of electron transport material on the interface modification layer;
[0015] (8) Thermally evaporate a hole blocking layer and a metal electrode on the electron transport material to complete the preparation of the perovskite solar cell.
[0016] Preferably, the interface modification layer material is one or more of ethylenediamine hydroiodide, phenethylammonium chloride or ethylenediamine hydrochloride, with a concentration of 0.5 to 2 mg / mL.
[0017] Preferably, the two-dimensional perovskite single crystal is prepared according to the following steps:
[0018] The two-dimensional single crystal precursor molecules are mixed with hydroiodic acid in a molar ratio of 1:(1-3), and 0.1-0.3 mL of ether is added for every 40 μL of the mixture to trigger crystallization; after washing, filtering, and drying, the single crystal precursor powder is obtained, which is then mixed with stannous chloride SnCl2 in a molar ratio of 1:(1-2) and added to the mixed solvent B. The mixture is heated at 90-100°C under continuous stirring until the solution turns bright yellow, and then cooled to room temperature to obtain a two-dimensional perovskite single crystal.
[0019] Preferably, the two-dimensional single crystal precursor molecule is one or more of 3-aminomethylpyridine or 3-aminomethylpiperidine;
[0020] Mixed solvent A is a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1;
[0021] The mixed solvent B is a hydroiodic acid aqueous solution and a hypophosphorous acid aqueous solution in a weight ratio of (55% to 60%): (45% to 55%).
[0022] Preferably, the hole transport layer material is poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS;
[0023] The film was spin-coated at a rotation speed of 4000-6000 rpm for 40-60 seconds and annealed at 120-140° C. for 20-30 minutes.
[0024] Preferably, in step (5), the tin-based perovskite film is deposited using an antisolvent method, comprising:
[0025] A perovskite precursor with a concentration of 0.8 to 1.5 mol / L is dropped onto an ITO transparent conductive glass deposited with a hole transport layer material, and spin-coated at a speed of 4000 to 8000 rpm in a nitrogen atmosphere for 40 to 80 seconds. An anti-solvent is added in the last 18 to 25 seconds, and annealed at 100 to 120° C. for 10 to 20 minutes to obtain a tin-based perovskite film; the anti-solvent is anhydrous chlorobenzene, toluene, ethyl acetate or ether.
[0026] Preferably, in step (6), the interface modification layer material is spin-coated on the tin-based perovskite film at a rotation speed of 4000-6000 rpm in a nitrogen atmosphere for 20-40 seconds, and annealed at 100-120° C. for 5-10 minutes.
[0027] As a preference, the evaporated electron transport layer is C 60 , thickness is 20~40nm;
[0028] The evaporated hole blocking layer is bathocuprol with a thickness of 5 to 10 nm;
[0029] The metal electrode Ag is evaporated to a thickness of 80 to 150 nm.
[0030] Another aspect of the present invention provides a perovskite solar cell based on a tin-based perovskite film prepared by the method described above.
[0031] The present invention adopts the above technical solution, which has the following beneficial effects:
[0032] (1) Optimizing the crystallization process: The present invention adds an appropriate proportion of two-dimensional perovskite single crystals to the tin-based perovskite precursor solution. Through the strong electrostatic and hydrogen bond interaction between the two-dimensional perovskite single crystals and the tin-based perovskite skeleton, it not only effectively regulates the distribution of the two-dimensional phase and the three-dimensional phase in the tin-based perovskite film, but also suppresses the Sn 2+ The oxidation and self-p-type doping of the film reduce the defect density and non-radiative loss in the film, slow down the crystallization rate, and optimize its crystallization process.
[0033] (2) Improve film quality: By using an optimized spin coating method and heat treatment process, high-quality two-dimensional / three-dimensional mixed-phase tin-based perovskite films with high flatness, few surface defects, and fast carrier extraction and transport were obtained.
[0034] (3) Improved water and oxygen barrier capability: The introduction of two-dimensional perovskite single crystals enables the prepared tin-based perovskite film to have excellent water and oxygen barrier capability, which can effectively prevent the intrusion of moisture and oxygen in the environment, thereby significantly improving the long-term stability of perovskite solar cells and extending the life of the device.
[0035] (4) Improved device performance: The efficiency and stability of the tin-based perovskite solar cells prepared using this invention are significantly improved. Compared with tin-based perovskite solar cells prepared without using two-dimensional perovskite single crystals, their maximum conversion efficiency increased from 10.91% to 13.28%, an increase of approximately 21.72%. After being placed in a nitrogen atmosphere without packaging for 3000 hours, the cell's photoelectric conversion efficiency still maintained approximately 96% of its initial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of this application, and do not constitute an improper limitation of the present invention. In the drawings:
[0037] FIG1( a ) is a SEM image of the tin-based perovskite film prepared in Comparative Example 1; FIG1( b ) is a SEM image of the tin-based perovskite film prepared in Example 1;
[0038] Figure 2XRD patterns of the tin-based perovskite films prepared in Comparative Example 1(a) and Example 1(b);
[0039] Figure 3 Fluorescence lifetime diagrams of the tin-based perovskite films prepared in Comparative Example 1(a) and Example 1(b);
[0040] FIG4( a ) is a transient absorption graph of the tin-based perovskite film prepared in Comparative Example 1; FIG4( b ) is a transient absorption graph of the tin-based perovskite film prepared in Example 1;
[0041] Figure 5 This is a structural diagram of a tin-based perovskite solar cell device prepared by the present invention;
[0042] Figure 6 JV curves of the low-dimensional tin-based perovskite solar cells prepared in Comparative Example 1(a) and Example 1(b);
[0043] Figure 7 Graph showing the change in photoelectric conversion efficiency over time for the tin-based perovskite solar cells prepared in Comparative Example 1(a) and Example 1(b). DETAILED DESCRIPTION
[0044] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0045] The method for preparing a perovskite solar cell based on a tin-based perovskite film provided in an embodiment of the present invention comprises the following specific steps:
[0046] Step 1: Soak the etched ITO conductive glass in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 20 to 30 minutes each, and then bake it in an oven to obtain a clean ITO substrate.
[0047] Step 2: dissolving the interface modification layer material ethylenediamine hydroiodide, phenethylammonium chloride or ethylenediamine hydrochloride in a mixed solvent of isopropanol and toluene to prepare an interface modification layer precursor solution of 0.5-2 mg / mL.
[0048] Step 3, dissolving the two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 according to a molar ratio of (0.01-0.05):(0.90-1.00):(0.90-1.00):(0.05-0.10):(0.10-0.50):(0.05-0.10), and stirring at room temperature for 3-5 hours to prepare a solution with a concentration of 0.8-1.5 mol L -1perovskite precursor solution.
[0049] The two-dimensional perovskite single crystal is prepared according to the following steps:
[0050] The two-dimensional single crystal precursor molecule 3-aminomethylpyridine or 3-aminomethylpiperidine is reacted with hydroiodic acid in a flask at a molar ratio of 1:(1-3), and 0.1-0.3 mL of ether is added for every 40 μL of the mixture, and then it is placed in a refrigerator to trigger crystallization; after washing with ether 3-5 times, filtering, and drying in a vacuum environment at 60-70°C for 12-15 hours, a single crystal precursor powder is obtained; it is then mixed with stannous chloride SnCl2 in a molar ratio of 1:(1-2) and added to a mixed solvent B (aqueous hydroiodic acid solution and an aqueous hypophosphorous acid solution with a weight ratio of (55%-60%):(45%-55%)), and heated to 90-100°C under continuous stirring until the solution turns bright yellow; the solution is then cooled to room temperature at a rate of 8-12°C / h to obtain a two-dimensional perovskite single crystal.
[0051] Step 4: Treat the ITO substrate cleaned in step 1 with UV ozone for 20 minutes, and spin-coat the hole transport material poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid PEDOT:PSS) on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0052] The hole transport material PEDOT:PSS is dropped onto the treated ITO conductive glass using a pipette, and spin-coated at a speed of 4000-6000 rpm for 40-60 seconds. The ITO coated with PEDOT:PSS is annealed at 120-140°C for 20-30 minutes.
[0053] Step 5: Drop a perovskite precursor solution with a concentration of 0.8 to 1.5 mol / L onto an ITO substrate deposited with a hole transport layer material, spin-coat at a speed of 4000 to 8000 rpm in a nitrogen atmosphere for 40 to 80 seconds, add an anti-solvent in the last 18 to 25 seconds, and then anneal at 100 to 120°C for 10 to 20 minutes to obtain a black tin-based perovskite film.
[0054] Wherein, the anti-solvent is anhydrous chlorobenzene, toluene, ethyl acetate or ether.
[0055] Step 6: spin-coat an interface modification layer material (ethylenediamine hydroiodide, phenethylammonium chloride or ethylenediamine hydrochloride) with a concentration of 0.5-2 mg / mL at a rotation speed of 4000-6000 rpm in a nitrogen atmosphere for 20-40 seconds, and anneal at 100-120° C. for 5-10 minutes.
[0056] Step 7: Vacuum thermal evaporation technology is used to evaporate 20-40nm C on the tin-based perovskite film in step 6. 60, to obtain an electron transport layer.
[0057] Step 8: Using vacuum thermal evaporation technology, evaporate a hole blocking layer bath copper with a thickness of 5 to 10 nm and a metal electrode Ag with a thickness of 80 to 150 nm on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0058] The present invention is further described below through different embodiments.
[0059] Example 1
[0060] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 20 to 30 minutes each, and then baked in an oven to obtain a clean ITO substrate.
[0061] Step 2) Dissolve the interface modification layer material ethylenediamine hydroiodide in a mixed solvent of isopropanol and toluene to prepare a 1 mg / mL interface modification layer precursor solution.
[0062] Step 3) The two-dimensional perovskite single crystal, formamidinium iodide, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide were dissolved in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 according to a molar ratio of 0.01:1.00:1.00:0.10:0.10:0.06, and stirred at room temperature for 4 hours to prepare a concentration of 0.9 mol L -1 perovskite precursor solution.
[0063] The two-dimensional perovskite single crystal is prepared according to the following steps:
[0064] The two-dimensional single crystal precursor molecule 3-aminomethylpyridine and hydroiodic acid are reacted in a flask at a molar ratio of 1:2. 0.2 mL of ether is added to every 40 μL of the mixture, and then the mixture is placed in a refrigerator to trigger crystallization. After washing with ether three times, filtering, and drying at 60°C in a vacuum environment for 15 hours, a single crystal precursor powder is obtained. The powder is then mixed with stannous chloride (SnCl2) at a molar ratio of 1:1 and added to a mixed solvent B (a 55%:45% weight ratio of hydroiodic acid aqueous solution and hypophosphorous acid aqueous solution). The mixture is heated to 95°C with continuous stirring until the solution turns bright yellow. The solution is then cooled to room temperature at a rate of 10°C / h to obtain a two-dimensional perovskite single crystal. Step 4) The cleaned ITO substrate in step 1 is treated with UV ozone for 20 minutes. The hole transport material poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS) is spin-coated on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0065] The hole transport material PEDOT:PSS was dropped onto the treated ITO conductive glass using a pipette and spin-coated at 4000 rpm for 50 seconds. The ITO coated with PEDOT:PSS was annealed at 140°C for 20 minutes.
[0066] Step 5) A perovskite precursor solution with a concentration of 0.9 mol / L was dropped onto an ITO substrate deposited with a hole transport layer material, and spin-coated at 8000 rpm for 60 seconds in a nitrogen atmosphere. Anti-solvent chlorobenzene was added in the last 18 to 25 seconds, followed by annealing at 100°C for 10 minutes to obtain a black tin-based perovskite film.
[0067] Step 6) Spin-coat ethylenediamine hydroiodide with a concentration of 1 mg / mL as the interface modification layer material at 5000 rpm in a nitrogen atmosphere for 30 seconds, and anneal at 100° C. for 5 minutes.
[0068] Step 7) Vacuum thermal evaporation technology is used to evaporate 20nm C on the tin-based perovskite film in step 6 60 , to obtain an electron transport layer.
[0069] Step 8) Using vacuum thermal evaporation technology, a hole blocking layer bath copper with a thickness of 10 nm and a metal electrode Ag with a thickness of 120 nm are evaporated on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0070] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this embodiment is 13.28%, the open circuit voltage is 0.78V, and the short circuit current is 23.31mA / cm 2 , the filling factor is 73.08%.
[0071] Example 2
[0072] Step 1) The etched ITO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then baked in an oven to obtain a clean ITO substrate.
[0073] Step 2) Dissolve the interface modification layer material ethylenediamine hydroiodide in a mixed solvent of isopropanol and toluene to prepare a 0.5 mg / mL interface modification layer precursor solution.
[0074] Step 3) The two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide were dissolved in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 according to a molar ratio of 0.02:0.90:0.90:0.08:0.30:0.05, and stirred at room temperature for 5 hours to prepare a concentration of 1.2 mol L -1 perovskite precursor solution.
[0075] Two-dimensional perovskite single crystals are prepared according to the following steps: the two-dimensional single crystal precursor molecule 3-aminomethylpyridine is reacted with hydroiodic acid in a flask at a molar ratio of 1:3, and 0.2 mL of ether is added for every 40 μL of the mixture, and then it is placed in a refrigerator to trigger crystallization; after washing with ether four times, filtering, and drying in a vacuum environment at 70°C for 12 hours, a single crystal precursor powder is obtained; it is then mixed with stannous chloride SnCl2 in a molar ratio of 1:1.5 and added to a mixed solvent B (a hydroiodic acid aqueous solution and a hypophosphorous acid aqueous solution with a weight ratio of 60%:40%), and heated to 90°C under continuous stirring until the solution turns bright yellow; the solution is then cooled to room temperature at a rate of 8°C / h to obtain a two-dimensional perovskite single crystal.
[0076] Step 4) The ITO substrate cleaned in step 1 is treated with UV ozone for 20 minutes, and a hole transport material poly (3,4-ethylenedioxythiophene): polystyrene sulfonate PEDOT:PSS is spin-coated on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0077] The hole transport material PEDOT:PSS was dropped onto the treated ITO conductive glass using a pipette and spin-coated at 5000 rpm for 50 seconds. The ITO coated with PEDOT:PSS was annealed at 130°C for 25 minutes.
[0078] Step 5) A 1.5 mol / L perovskite precursor solution was dropped onto an ITO substrate deposited with a hole transport layer material, and spin-coated at 6000 rpm for 40 seconds in a nitrogen atmosphere. Anti-solvent toluene was added in the last 18 to 25 seconds, followed by annealing at 120°C for 10 minutes to obtain a black tin-based perovskite film.
[0079] Step 6) Spin-coat ethylenediamine hydrochloride with a concentration of mg / mL as the interface modification layer material at 4000 rpm in a nitrogen atmosphere for 40 seconds, and anneal at 100° C. for 10 minutes.
[0080] Step 7) Vacuum thermal evaporation technology is used to evaporate 30nm C on the tin-based perovskite film in step 6 60 , to obtain an electron transport layer.
[0081] Step 8) Using vacuum thermal evaporation technology, a hole blocking layer of bathocuprol with a thickness of 5 nm and a metal electrode Ag with a thickness of 150 nm are evaporated on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0082] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this embodiment is 12.94%, the open circuit voltage is 0.78V, and the short circuit current is 22.93mA / cm 2 , the filling factor is 72.35%.
[0083] Example 3
[0084] Step 1) The etched ITO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 25 minutes each, and then baked in an oven to obtain a clean ITO substrate.
[0085] Step 2) Dissolve the interface modification layer material ethylenediamine hydroiodide in a mixed solvent of isopropanol and toluene to prepare a 1.5 mg / mL interface modification layer precursor solution.
[0086] Step 3) The two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide were dissolved in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 according to a molar ratio of 0.04:1.00:1.00:0.05:0.10:0.07, and stirred at room temperature for 3 hours to prepare a concentration of 1.5 mol L -1 perovskite precursor solution.
[0087] The two-dimensional perovskite single crystal is prepared according to the following steps:
[0088] The two-dimensional single crystal precursor molecule 3-aminomethylpiperidine was reacted with hydroiodic acid in a flask in a molar ratio of 1:1, and 0.3 mL of ether was added for every 40 μL of the mixture, which was then placed in a refrigerator to trigger crystallization; after washing with ether five times, filtering, and drying in a vacuum environment at 65°C for 14 hours, a single crystal precursor powder was obtained; it was then mixed with stannous chloride SnCl2 in a molar ratio of 1:2 and added to a mixed solvent B (a hydroiodic acid aqueous solution and a hypophosphorous acid aqueous solution with a weight ratio of 57%:43%), and heated to 100°C under continuous stirring until the solution turned bright yellow; the solution was then cooled to room temperature at a rate of 9°C / h to obtain a two-dimensional perovskite single crystal.
[0089] Step 4) The ITO substrate cleaned in step 1 is treated with UV ozone for 20 minutes, and a hole transport material poly (3,4-ethylenedioxythiophene): polystyrene sulfonate PEDOT:PSS is spin-coated on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0090] The hole transport material PEDOT:PSS was dropped onto the treated ITO conductive glass using a pipette and spin-coated at 4000 rpm for 60 seconds. The ITO coated with PEDOT:PSS was annealed at 140°C for 20 minutes.
[0091] Step 5) A 0.8 mol / L perovskite precursor solution was dropped onto an ITO substrate deposited with a hole transport layer material, and spin-coated at 4000 rpm for 80 seconds in a nitrogen atmosphere. Anti-solvent ethyl acetate was added in the last 18 to 25 seconds, followed by annealing at 110°C for 15 minutes to obtain a black tin-based perovskite film.
[0092] Step 6) Spin-coat 1.5 mg / mL interface modification layer material, phenylethylammonium chloride, at 4500 rpm in a nitrogen atmosphere for 30 seconds, and anneal at 120° C. for 5 minutes.
[0093] Step 7) Vacuum thermal evaporation technology is used to evaporate 40nm C on the tin-based perovskite film in step 6 60 , to obtain an electron transport layer.
[0094] Step 8) Using vacuum thermal evaporation technology, a hole blocking layer of bath copper with a thickness of 8 nm and a metal electrode Ag with a thickness of 100 nm are evaporated on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0095] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this embodiment is 12.72%, the open circuit voltage is 0.76V, and the short circuit current is 23.06mA / cm 2 , the filling factor is 72.59%.
[0096] Example 4
[0097] Step 1) The etched ITO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then baked in an oven to obtain a clean ITO substrate.
[0098] Step 2) Dissolve the interface modification layer material ethylenediamine hydroiodide in a mixed solvent of isopropanol and toluene to prepare a 2 mg / mL interface modification layer precursor solution.
[0099] Step 3) The two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide were dissolved in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 according to a molar ratio of 0.05:0.90:0.90:0.09:0.50:0.10, and stirred at room temperature for 4 hours to prepare a concentration of 0.8 mol L -1 perovskite precursor solution.
[0100] The two-dimensional perovskite single crystal is prepared according to the following steps:
[0101] The two-dimensional single crystal precursor molecule 3-aminomethylpiperidine was reacted with hydroiodic acid in a flask at a molar ratio of 1:1.5, and 0.2 mL of ether was added for every 40 μL of the mixture, which was then placed in a refrigerator to trigger crystallization; after washing with ether four times, filtering, and drying in a vacuum environment at 70°C for 13 hours, a single crystal precursor powder was obtained; it was then mixed with stannous chloride SnCl2 in a molar ratio of 1:1 and added to a mixed solvent B (aqueous hydroiodic acid solution and an aqueous hypophosphorous acid solution with a weight ratio of 58%:42%), and heated to 90°C under continuous stirring until the solution turned bright yellow; the solution was then cooled to room temperature at a rate of 12°C / h to obtain a two-dimensional perovskite single crystal.
[0102] Step 4) The ITO substrate cleaned in step 1 is treated with UV ozone for 20 minutes, and a hole transport material poly (3,4-ethylenedioxythiophene): polystyrene sulfonate PEDOT:PSS is spin-coated on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0103] The hole transport material PEDOT:PSS was dropped onto the treated ITO conductive glass using a pipette and spin-coated at 4500 rpm for 55 s. The ITO coated with PEDOT:PSS was annealed at 140°C for 25 min.
[0104] Step 5) A 1.2 mol / L perovskite precursor solution was dropped onto an ITO substrate deposited with a hole transport layer material, and spin-coated at 5500 rpm for 45 seconds in a nitrogen atmosphere. Anti-solvent ether was added in the last 18 to 25 seconds, followed by annealing at 120°C for 15 minutes to obtain a black tin-based perovskite film.
[0105] Step 6) Spin-coat 0.5 mg / mL of ethylenediamine hydroiodide, an interface modification layer material, at 6000 rpm in a nitrogen atmosphere for 20 seconds, and anneal at 100° C. for 8 minutes.
[0106] Step 7) Vacuum thermal evaporation technology is used to evaporate 25nm C on the tin-based perovskite film in step 6 60 , to obtain an electron transport layer.
[0107] Step 8) Using vacuum thermal evaporation technology, a hole blocking layer bath copper with a thickness of 9 nm and a metal electrode Ag with a thickness of 80 nm are evaporated on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0108] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this embodiment is 12.09%, the open circuit voltage is 0.76V, and the short circuit current is 22.21mA / cm 2 , the filling factor is 71.68%.
[0109] The following is a comparison of the inverted planar tin-based perovskite solar cells prepared in Comparative Example 1 and Example 1 as an example to fully understand the present invention.
[0110] Comparative Example 1
[0111] Step 1) The etched ITO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 20 minutes each, and then baked in an oven to obtain a clean ITO substrate;
[0112] Step 2) Dissolve the interface modification layer material ethylenediamine hydroiodide in a mixed solvent of isopropanol and toluene to prepare a 1 mg / mL interface modification layer precursor solution.
[0113] Step 3) Formamidinium iodide, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide were dissolved in a mixed solvent A of N,N-dimethylformamide and dimethylsulfoxide in a volume ratio of 4:1 at a molar ratio of 1.00:1.00:0.10:0.10:0.06, and stirred at room temperature for 4 h to prepare a solution with a concentration of 0.9 mol L -1 perovskite precursor solution.
[0114] Step 4) The ITO substrate cleaned in step 1 is treated with UV ozone for 20 minutes, and a hole transport material poly (3,4-ethylenedioxythiophene): polystyrene sulfonate PEDOT:PSS is spin-coated on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer.
[0115] The hole transport material PEDOT:PSS was dropped onto the treated ITO conductive glass using a pipette and spin-coated at 4000 rpm for 50 seconds. The ITO coated with PEDOT:PSS was annealed at 140°C for 20 minutes.
[0116] Step 5) A perovskite precursor solution with a concentration of 0.9 mol / L was dropped onto an ITO substrate deposited with a hole transport layer material, and spin-coated at 8000 rpm for 60 seconds in a nitrogen atmosphere. Anti-solvent chlorobenzene was added in the last 18 to 25 seconds, followed by annealing at 100°C for 10 minutes to obtain a black tin-based perovskite film.
[0117] Step 6) Spin-coat ethylenediamine hydroiodide with a concentration of 1 mg / mL as the interface modification layer material at 5000 rpm in a nitrogen atmosphere for 30 seconds, and anneal at 100° C. for 5 minutes.
[0118] Step 7) Vacuum thermal evaporation technology is used to evaporate 20nm C on the tin-based perovskite film in step 6 60 , to obtain an electron transport layer.
[0119] Step 8) Using vacuum thermal evaporation technology, a hole blocking layer bath copper with a thickness of 10 nm and a metal electrode Ag with a thickness of 120 nm are evaporated on the electron transport layer in step 7 to obtain a tin-based perovskite solar cell.
[0120] Figures 1(a) and (b) are SEM images of the tin-based perovskite films prepared in Comparative Example 1 and Example 1. After adding two-dimensional perovskite single crystals to the precursor, the average grain size of the film increased from ~0.40 μm to ~0.45 μm, indicating that the crystallization rate slowed down and the quality of the resulting film became higher.
[0121] Figure 2 (a) and (b) are the XRD patterns of the tin-based perovskite films prepared in Comparative Example 1 and Example 1, respectively, which further show that after adding two-dimensional perovskite single crystals to the precursor, the diffraction peak intensity becomes higher, indicating that the crystallinity of the film becomes higher and the quality of the obtained film is improved.
[0122] Figure 3 (a) and (b) are the fluorescence lifetime diagrams of the tin-based perovskite films prepared in Comparative Example 1 and Example 1, respectively. It can be seen that the tin-based perovskite film absorption layer prepared in Example 1 increases the carrier lifetime from 3.94ns to 15.81ns, indicating that the defect state density in the film is reduced.
[0123] Figures 4(a) and (b) are transient absorption diagrams of the tin-based perovskite films prepared in Comparative Example 1 and Example 1. It can be seen that compared with Comparative Example 1, the two-dimensional phase content in the tin-based perovskite film prepared in Example 1 is reduced, and the three-dimensional phase content is increased, indicating that the addition of the two-dimensional perovskite single crystal 3AMPYSnI4 successfully regulates the phase distribution in the tin-based perovskite film, which is beneficial to the improvement of the photovoltaic performance of the device.
[0124] Figure 5 This is a diagram of the structure of the tin-based perovskite solar cell device prepared in Example 1. From bottom to top, it includes an ITO conductive substrate, a hole transport layer, a tin-based perovskite thin film light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode layer.
[0125] Figure 6 (a) and (b) are JV curves of the low-dimensional tin-based perovskite solar cells prepared in Comparative Example 1 and Example 1, respectively. The photovoltaic performance of the perovskite solar cell prepared in Example 1 is significantly better than that of Comparative Example 1.
[0126] Figure 7This is a graph showing the photoelectric conversion efficiency of the tin-based perovskite solar cells prepared in Comparative Example 1 and Example 1 over time. It can be seen that the stability of the device with the addition of two-dimensional perovskite single crystals is significantly improved, and after storage in a nitrogen atmosphere for more than 3000 hours, it still maintains about 96% of the initial efficiency.
[0127] From the above examples, it can be seen that the photoelectric conversion efficiency of the solar cell device prepared by the present invention is as high as 13.28%, the open circuit voltage is as high as 0.78V, and the short circuit current can reach 23.31mA / cm 2 , with a maximum fill factor of 73.08%. It has a good crystallization process, excellent carrier extraction and transmission capabilities, a flat and dense surface, and good water and oxygen barrier capabilities, which greatly improves the photoelectric conversion efficiency and device stability of perovskite solar cells.
[0128] This method can significantly optimize the distribution of two-dimensional and three-dimensional phases in tin-based perovskite films, slow down the crystallization rate of the film, increase the carrier extraction and transmission rate, reduce the defect state density, and enhance the long-term stability of the device. The present invention prepares a tin-based perovskite film by adding a two-dimensional perovskite single crystal to a precursor solution of a tin-based perovskite and using an anti-solvent method. The addition of the two-dimensional perovskite single crystal molecules helps to regulate the phase distribution of the film, reduce the crystallization rate, reduce non-radiative recombination, and promote interface carrier extraction and transmission. The tin-based perovskite solar cell prepared based on the present invention has excellent photoelectric conversion efficiency and outstanding water and oxygen blocking ability, which significantly improves the environmental stability of the device.
[0129] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solutions disclosed in the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features therein according to the disclosed technical content without creative labor, and these substitutions and modifications are all within the protection scope of the present invention.
Claims
1. A method for preparing a perovskite solar cell based on a tin-based perovskite film, characterized in that: The following steps are involved: (1) Cleaning and baking the etched ITO conductive glass to obtain a clean ITO substrate; (2) dissolving the interface modification layer material in a mixed solvent of isopropanol and toluene to prepare an interface modification layer precursor solution; (3) dissolving a two-dimensional perovskite single crystal, formamidine iodine, stannous iodide, germanium iodide, stannous fluoride and phenethylammonium bromide in a mixed solvent A in a molar ratio of (0.01-0.05):(0.90-1.00):(0.90-1.00):(0.05-0.10):(0.10-0.50):(0.05-0.10) to prepare a tin-based perovskite precursor solution; (4) spin coating a hole transport layer material on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer; (5) spin coating a tin-based perovskite precursor solution on an ITO transparent conductive glass deposited with a hole transport layer material using an anti-solvent method, and annealing to obtain a tin-based perovskite film; (6) spin coating an interface modification layer material on the tin-based perovskite film to deposit an interface modification layer; (7) vacuum thermal evaporation of electron transport material on the interface modification layer; (8) Thermally evaporate a hole blocking layer and a metal electrode on the electron transport material to complete the preparation of the perovskite solar cell.
2. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: The interface modification layer material is one or more of ethylenediamine hydroiodide, phenethylammonium chloride or ethylenediamine hydrochloride, and the concentration is 0.5-2 mg / mL.
3. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: The two-dimensional perovskite single crystal is prepared according to the following steps: Mix the two-dimensional single crystal precursor molecule with hydroiodic acid in a molar ratio of 1:(1-3), and add 0.1-0.3 mL of ether per 40 μL of the mixture to trigger crystallization; After washing, filtering and drying, a single crystal precursor powder is obtained, which is then mixed with stannous chloride SnCl2 in a molar ratio of 1:(1-2) and added to a mixed solvent B. The mixture is heated to 90-100°C under continuous stirring until the solution turns bright yellow and cooled to room temperature to obtain a two-dimensional perovskite single crystal.
4. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 3, characterized in that: The two-dimensional single crystal precursor molecule is one or more of 3-aminomethylpyridine or 3-aminomethylpiperidine; The mixed solvent A is a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1; The mixed solvent B is a hydroiodic acid aqueous solution and a hypophosphorous acid aqueous solution in a weight ratio of (55% to 60%): (45% to 55%).
5. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: The hole transport layer material is poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS; Spin coating is performed at a rotation speed of 4000-6000 rpm for 40-60 seconds, and annealing is performed at 120-140° C. for 20-30 minutes.
6. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: In step (5), a tin-based perovskite film is deposited by an anti-solvent method, comprising: A perovskite precursor with a concentration of 0.8 to 1.5 mol / L is dropped onto an ITO transparent conductive glass deposited with a hole transport layer material, and spin-coated at a rotation speed of 4000 to 8000 rpm in a nitrogen atmosphere for 40 to 80 seconds. An anti-solvent is added in the last 18 to 25 seconds, and annealed at 100 to 120° C. for 10 to 20 minutes to obtain a tin-based perovskite film.
7. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 6, characterized in that: The anti-solvent is anhydrous chlorobenzene, toluene, ethyl acetate or ether.
8. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: In step (6), the interface modification layer material is spin-coated on the tin-based perovskite film at a rotation speed of 4000-6000 rpm in a nitrogen atmosphere for 20-40 seconds, and annealed at 100-120° C. for 5-10 minutes.
9. The method for preparing a perovskite solar cell based on a tin-based perovskite film according to claim 1, characterized in that: The evaporated electron transport layer is C 60 , thickness is 20~40nm; The evaporated hole blocking layer is bathocuproin with a thickness of 5 to 10 nm; The metal electrode Ag is evaporated to a thickness of 80 to 150 nm.
10. A perovskite solar cell based on a tin-based perovskite film prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-dimensional tin-based perovskite thin film prepared from ionic liquid type organic large-volume amine molecular salt as well as solar cell and application of low-dimensional tin-based perovskite thin film
CN111952455A
Preparation method and application of bifunctional ionic salt passivated tin-based perovskite thin film and perovskite solar cell of bifunctional ionic salt passivated tin-based perovskite thin film
CN114284440A
Halide perovskite solar cell and bottom interface self-growth modification method therefor
WO2023155562A1
Cited By
Preparation method of donor-receptor interaction two-dimensional perovskite solar cell material
CN120857831A